THE ROLE OF JAWI TAFSIR IN SOCIO-CULTURAL TRANSFORMATION OF THE NUSANTARA ISLAM: A STUDY ON TARJUMÄ€N AL-MUSTAFÄªD - Putra, D. I. Ansusa; Zikwan, Zikwan (Center for Research and Development of Religious Literature and Heritage, 2019)
The attention of researchers about Islam to Nusantara is largely related to the transmission of Islam to Nusantara. Meanwhile, attention to the role of vernacularization of Islamic sciences by Nusantara scholars - including attention to vernacularization of interpretive science - is still limited. This paper with the vernacular concept from A.H. Johns, focused on discussing the role of Jawi Tafsir in the Islamization of Nusantara in the early phases of both the formulation of Islamic Nusantara Islam and the socio-cultural transformation of Nusantara. This article?s frame of reference is in terms of the concepts of enculturation, adoption and cultural adaptation, in which vernacularization occurs in each of these processes. Through studies on the Jawi?s vernacular interpretation, Tarjum?n al-Mustaf?d, this paper argues that in the early scientific formulation of the Nusantara Islam that transformed the socio-cultural Nusantara, the existence of the Tarjum?n al-Mustaf?d had a major role. With another Jawi commentaries, Tarjum?n al-Mustaf?d then became the Nusantara's Islamic identity and proof of Islam with the archipelago's character.